Socioeconomic Drivers of Women’s Saving Behavior: Evidence from Cooperatives in Birendranagar, Surkhet, Nepal - Vasishtha, Veetihotra (Journal of Nepalese Management and Research, 2025)
This study investigates the socioeconomic factors influencing women’s saving behavior in cooperatives of Birendranagar, Surkhet, Nepal, focusing on financial knowledge, self-control, family and peer influence, and saving intention as predictors, with saving behavior as the dependent variable. Grounded in the Theory of Planned Behavior, the research employed a cross-sectional quantitative design, collecting data from 152 women of savings and credit cooperatives of Birendranagar are selected through purposive sampling design, using a structured questionnaire. The study revealed that financial knowledge (β = 0.285816, p = 0.0001), self-control (β = 0.274769, p = 0.0421), and saving intention (β = 0.137477, p = 0.0195) significantly and positively affect saving behavior, explaining 83.98% of its variance (R-squared = 0.839757). However, family and peer influence (β = 0.121741, p = 0.8667) showed have no significant effect, possibly due to moderate multicollinearity (VIF < 5) among predictors. Diagnostic tests confirmed the model’s validity, with no significant issues in linearity, normality, homoscedasticity, autocorrelation, or specification. The findings highlight the critical role of financial literacy, self-discipline, and planning in promoting women’s saving practices, offering practical insights for cooperative-based interventions to enhance financial empowerment in semi-urban Nepal.